Understanding Mashup Development - Jin Yu; Benatallah, B.; Casati, F.; Daniel, F. (IEEE internet computing, 2008)
Web mashups are Web applications developed using contents and services available online. Despite rapidly increasing interest in mashups, comprehensive development tools and frameworks are lacking, and in most cases mashing up a new application implies a significant manual programming effort. This article overviews current tools, frameworks, and trends that aim to facilitate mashup development. The authors use a set of characteristic dimensions to highlight the strengths and weaknesses of some representative approaches.